Pemanfaatan Perpustakaan Digital Sebagai Sumber Belajar Elektronik Masa Pandemi COVID-19 di SMA Negeri 3 Batam - Rayhan Musa Novian; Noviandi Harahap (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2022)
The Indonesian government, through the Ministry of Education and Culture, has appealed to all schools to carry out online learning as stated in the Circular of the Minister of Education and Culture of the Republic of Indonesia Number 4 of 2020 concerning the Implementation of Education in the Emergency Coronavirus Disease (COVID-19). As a result, many students find it difficult to undergo the learning process online due to limited electronic learning resources. Departing from this problem, it is necessary to have a digital library that can be used as a learning resource to optimize the online learning process. This research was carried out using descriptive quantitative methods involving SMA Negeri 3 Batam students as research subjects. Based on the data obtained, it is known that as many as 31.80% of students find it difficult to get learning resources during the online learning process. Therefore, presenting a digital library is the right step to optimize online learning during the COVID-19 pandemic..